Cardy-Verlinde Formula and Its Self-Gravitational Corrections for Regular Black Holes - M. Sharif; Rabia Saleem (Advances in High Energy Physics)
We check the consistency of the entropy of Bardeen and Ayón Beato-García-Bronnikov black holes with the entropy of particular conformal field theory via Cardy-Verlinde formula. We also compute the first-order semiclassical corrections of this formula due to self-gravitational effects by modifying pure extensive and Casimir energy in the context of Keski-Vakkuri, Kraus and Wilczek analysis. It is concluded that the correction term remains positive for both black holes, which leads to the violation of the holographic bound.